A randomized, blinded, placebo‐controlled trial of education and iron supplementation for mitigation of iron deficiency in regular blood donors. Issue 6 (26th January 2016) - Mast, Alan E.; Bialkowski, Walter; Bryant, Barbara J.; Wright, David J.; Birch, Rebecca; Kiss, Joseph E.; D'Andrea, Pam; Cable, Ritchard G.; Spencer, Bryan R.
Abstract : BACKGROUND: The historical approach of offering dietary advice to donors with low hemoglobin (Hb) is ineffective for preventing iron deficiency in frequent donors. Alternative approaches to maintaining donor iron status were explored. STUDY DESIGN AND METHODS: Frequent blood donors were randomly assigned into five arms for 2 years of follow‐up. Three double‐blinded arms provided 60 once‐daily pills after each donation (38, 19, or 0 mg of iron). Two single‐blinded arms provided iron status (ferritin) or no information letters after each donation. Ferritin, soluble transferrin receptor, and complete blood count were measured at each donation. RESULTS: There were 692 subjects enrolled and 393 completed the study. Subjects in pill groups deenrolled more than those in letter groups (39% vs. 7%). Adverse events occurred equally in subjects receiving iron or placebo pills. Of those completing the study, the prevalence of ferritin of less than 12 or less than 26 ng/mL declined by more than 50% and was statistically indistinguishable in the three intervention groups (19 or 38 mg of iron; iron status letter). Longitudinal analyses of all subjects showed improved iron status in iron pill groups and worsening iron status in control groups (placebo; no information letter). The iron pill groups experienced a net increase of approximately 0.6 g/dL Hb compared to control groups. The iron status letter group had little change in Hb. CONCLUSION: Providing 19 or 38 mg of daily iron or iron status information were effective and mostly equivalent interventions for mitigating iron deficiency in regular donors when compared at the end of the 2‐year longitudinal phase of the study. Donors without intervention had worsened iron deficiency with continued donation.